2020
DOI: 10.1038/s41467-020-18479-5
|View full text |Cite
|
Sign up to set email alerts
|

Summer warming explains widespread but not uniform greening in the Arctic tundra biome

Abstract: Arctic warming can influence tundra ecosystem function with consequences for climate feedbacks, wildlife and human communities. Yet ecological change across the Arctic tundra biome remains poorly quantified due to field measurement limitations and reliance on coarse-resolution satellite data. Here, we assess decadal changes in Arctic tundra greenness using time series from the 30 m resolution Landsat satellites. From 1985 to 2016 tundra greenness increased (greening) at ~37.3% of sampling sites and decreased (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
237
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(308 citation statements)
references
References 104 publications
22
237
2
Order By: Relevance
“…Our results highlight that at finer spatial resolution, the relationship between satellite-derived spectra and biomass is not straightforward. This has implications for the observed Arctic greening or browning (Myers-Smith et al 2020;Berner et al 2020), as our results suggest that an increase in NDVI is not necessarily linked to increased biomass. This further complicates the interpretation of greening patterns (Myers-Smith et al 2020).…”
Section: Discussionmentioning
confidence: 74%
“…Our results highlight that at finer spatial resolution, the relationship between satellite-derived spectra and biomass is not straightforward. This has implications for the observed Arctic greening or browning (Myers-Smith et al 2020;Berner et al 2020), as our results suggest that an increase in NDVI is not necessarily linked to increased biomass. This further complicates the interpretation of greening patterns (Myers-Smith et al 2020).…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies based on remote sensing data or field simulation experiments have provided strong evidence that greening across Siberia is mainly driven by warming (Elmendorf et al 2012;Phoenix & Bjerke 2016). However, some studies have also indicated that the effect of warming on vegetation depends on soil moisture, with more positive effects in humid regions (Berner et al 2020). In other cases, changes in surface albedo, permafrost and soil nutrients could also influence the vegetation response to warming and even affect the key environmental constraints that limit vegetation activities (Myers-Smith et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation greenness in Siberia has been observed to increase with climate warming, especially in regions primarily characterized by tundra shrubs, where considerable greening has been reported (Forbes, Fauria & Zetterberg 2010;Berner et al 2020). In the boreal forests and grasslands, the greening trend was relatively small (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have demonstrated a "greening" trend in vegetation cover both globally [85][86][87] and regionally, from the Arctic [88] to the tropics [85]. While obvious increases in vegetation greenness are associated with anthropogenic land use and land cover change (LULCC), such as expansion of irrigated agriculture and afforestation, greening is also occurring in regions with less direct human influence [85,88]. Potential causes of such increases involve nitrogen deposition [87], CO2 fertilization, and climate change [85].…”
Section: Discussionmentioning
confidence: 99%